Learning disabilities and related mild disabilities : teaching strategies and new directions - Lerner, Janet W.; Beverley H. Johns (Unites States of America : Wadsworth Cengage Learning, 2012)
This book focuses both on students with learning disabilities and on students with mild disabilities . It provides a comprehensive view of the field, describes the characteristics of various mild disabilities and offers teaching strategies for general education teachers.
1. Learning disabilities and related mild disabilities : characteristics and current directions -- 2. Assessment and the IEP process -- 3. Clinical teaching -- 4. Educational settings and the role of the family -- 5. Theories of learning : implications of teaching -- 6. Social, emotional, and behavioral challenges -- 7. Attention deficit hyperactivity disorder and autism spectrum disorders -- 8. Young children with disabilities -- 9. Adolescents and adults with learning disabilities and mild disabilities -- 10. Medical aspects of learning disabilities and related mild disabilities -- 11. Spoken language difficulties : listening and speaking -- 12. Reading difficulties -- 13. Written language : written expression, spelling, and handwriting -- 14. Mathematics difficulties .
Includes bibliographical references and index.
Keywords: DISABILITIES